Role of cardiometabolic risk in the association between accumulation of affective symptoms across adulthood and mid-life cognitive function: national cohort study. (May 2021) - John, Amber; Desai, Roopal; Richards, Marcus; Gaysina, Darya; Stott, Joshua
Abstract : Background: Affective symptoms are associated with cognition in mid-life and later life. However, the role of cardiometabolic risk in this association has not been previously examined. Aims: To investigate how cardiometabolic risk contributes to associations between affective symptoms and mid-life cognition. Method: Data were used from the National Child Development Study (NCDS), a sample of people born in Britain during one week in 1958. Measures of immediate and delayed memory, verbal fluency and information processing speed and accuracy were available at age 50. Affective symptoms were assessed at ages 23, 33 and 42 years and a measure of accumulation was derived. A cardiometabolic risk score was calculated from nine cardiometabolic biomarkers at age 44. Path models were run to test these associations, adjusting for sex, education, socioeconomic position and affective symptoms at age 50. Results: After accounting for missing data using multiple imputation, path models indicated significant indirect associations between affective symptoms and mid-life immediate memory (β = −0.002, s.e. = 0.001, P = 0.009), delayed memory (β = −0.002, s.e. = 0.001, P = 0.02) and verbal fluency (β = −0.002, s.e. = 0.001, P = 0.045) through cardiometabolic risk. Conclusions: These findings suggest that cardiometabolic risk may play an important role in the association between affective symptoms and cognitive function (memory and verbal fluency). Results contribute to understanding of biological mechanisms underlying associations between affective symptoms and cognitive ageing, which can have implications for early detection of, and intervention for, those at risk of poorer cognitive outcomes.